Capital Accumulation, Trade Liberalization and Rising Wage Inequality: The Case of Argentina - Leonardo Gasparini; Pablo Acosta (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2004)
Capital accumulation can modify the relative productivity between skilled and unskilled workers, thus leading to changes in the wage structure. In particular, if capital goods are relatively more complementary to skilled workers in the production function (skill-biased technologies), a positive correlation between investment in physical capital and the wage premium would be expected. In this paper we present evidence for this hypothesis by taking advantage of the variability in wage premia and capital investment across industries in the Argentine manufacturing sector. We conclude that the wage premium for workers with complete college education increased more in those industries with higher investment in machinery and equipment. As in Galiani and Sanguinetti (2003, in this journal), the wage premium also grew more in those sectors which faced strong import competition, although this effect is empirically less relevant than the capital accumulation effect.
Keywords: J31; F16; O33; 330; wage premium; capital accumulation; technological change; trade liberalization; wage inequality; Argentina.